An observational study on blood pressure measurement discrepancies between left and right arms among Indonesian nursing students - Safira, Ekatiara Siva; Sarwono, Bambang; Kriswoyo, Pramono Giri (Innovation in Health for Society, 2024)
Blood pressure is crucial in healthcare, and measurement deviations can lead to diagnostic errors and incorrect treatment. Additionally, blood pressure helps detect various cardiovascular diseases. Most people measure blood pressure in only one arm, neglecting the other. However, blood pressure readings can vary due to many factors. This research aims to measure differences in blood pressure between the left and right arms, specifically systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP). The study employed a quantitative approach with a comparative observational analysis design. Probability sampling, specifically proportional stratified random sampling, was used for sample selection. A digital blood pressure monitor was utilized for measurements. Data analysis was performed using the Wilcoxon surrogate test. The statistical Wilcoxon test showed a mean difference of 0.002 (p<0.05) in the SBP measurements, indicating a significant difference between right and left-arm SBP measurements. The systolic blood pressure in the right arm was 102.37 mmHg, which was 1.66 mmHg higher than that measured in the left arm. While there is a difference in the average systolic, diastolic, and MAP results between the left and right arms, it is insignificant. However, the right arm's systolic blood pressure (SBP) is notably higher than the left. Keywords: Blood pressure measurements; hypertension; health assessment; innovation; healthcare delivery